General provisions of constitutional modernization of the judicial system as an objective social and legal process - Horodovenko, Artur (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The main national and foreign constitutional bases of judicial power are analyzed. The constitutional and legal regulation of the judiciary in European countries has a number of peculiaritiesIt was explored. The role of the court in the system of separation of powers is determined mainly by its powers to control the legality of the activities of other branches of governmentIt was determined.